Battling an African cattle killer: Why East Coast fever matters - Kiara, Henry K. (International Livestock Research Institute, 2014)
Henry Kiara, a veterinary epidemiologist at ILRI talks about the risk posed by East Coast fever and how a vaccine against the disease helps protect cattle in the continent.